2011
DOI: 10.1007/s00213-011-2293-5
|View full text |Cite
|
Sign up to set email alerts
|

Fluvoxamine enhances prefrontal dopaminergic neurotransmission in adrenalectomized/castrated mice via both 5-HT reuptake inhibition and σ1 receptor activation

Abstract: These findings suggest that fluvoxamine enhances prefrontal dopaminergic neurotransmission via both 5-HT reuptake inhibition and σ(1) receptor activation under the circulating neuroactive steroid-deficient conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 54 publications
(56 reference statements)
0
23
0
Order By: Relevance
“…The neuronal-activity-marker c-Fos was determined 2 h after the encounter in the brains of male group-and isolation-reared mice, as described previously (Ago et al, 2011;Koda et al, 2010). Mice that were not exposed to an intruder were used as controls (Figure 2).…”
Section: C-fos Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…The neuronal-activity-marker c-Fos was determined 2 h after the encounter in the brains of male group-and isolation-reared mice, as described previously (Ago et al, 2011;Koda et al, 2010). Mice that were not exposed to an intruder were used as controls (Figure 2).…”
Section: C-fos Immunohistochemistrymentioning
confidence: 99%
“…Four independent sections per animal containing the prefrontal cortex, nucleus accumbens, amygdala, dorsal raphe nucleus, or ventral tegmental area were selected. Then, c-Fos-positive nuclei were counted manually by experienced observers blinded to the rearing and encounter conditions of the animals, under bright-field illumination using a Keyence microscope (BIOREVO, BZ-9000) (Ago et al, 2011;Koda et al, 2010). The number of c-Fos-positive nuclei in each section was determined in a 500 Â 500 mm 2 area in the left and right hemispheres and averaged using an ImageJ 1.41 software package (NIH, Bethesda, MD, USA).…”
Section: C-fos Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of sigma-1 receptors for the antidepressant effect of fluvoxamine is still unclear, as under physiological conditions, a fluvoxamine induced increase in prefrontal cortex extracellular levels of 5-HT, dopamine and noradrenaline is independent on sigma-1 receptors [45].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the dopaminergic neurons have 5-HT receptors that permit the tonic control of dopamine release in the midbrain, striatum and nucleus accumbens [48]. It has been shown that systemic fluvoxamine administration induced a moderate increase in extracellular dopamine levels in the prefrontal cortex of rats [49] and mice [45], and the dorsal striatum of rats [50], but did not influence dopamine levels in the thalamus [50] of rats. The unchanged 5-HT synthesis rate in the nerve terminals following acute fluvoxamine administration could be explained by a fluvoxamine effect on extracellular dopamine levels at least in the area of dopaminergic nerve terminals like the striatum.…”
Section: Discussionmentioning
confidence: 99%